Capital Allocation Strategies for Fleet Decarbonization: A Financial Risk-Return Analysis of Alternative Fuel Investment Among Global Shipping Enterprises - Tri Kismantoro (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The global shipping industry's transition toward decarbonization demands unprecedented capital reallocation, compelling shipping enterprises to make high-stakes investment decisions under conditions of regulatory uncertainty, technological immaturity, and volatile fuel markets. This study investigates how global shipping companies develop capital allocation strategies for fleet decarbonization, with particular focus on the financial risk-return dynamics associated with investments in alternative fuels including liquefied natural gas (LNG), methanol, and ammonia propulsion systems. Employing a qualitative research design anchored in thematic analysis, the study engages thirty senior financial, operational, and strategic management professionals across global shipping enterprises, financial institutions, and maritime regulatory organizations. Findings reveal four strategic archetypes of decarbonization capital allocation and identify green financing instruments — including sustainability-linked bonds and green ship financing — as critical enablers of investment feasibility. The study advances maritime financial management scholarship by mapping the structural relationships between regulatory pressure, financial risk appetite, and capital strategy in the global decarbonization transition.